Reflections of different styles of music based on emotions and feelings with high school band - Shelton, Erin Elissa (Kansas State University, 2021)
The lessons demonstrated in this report show the high school band listening, performing, and reflecting on distinctive styles of music and the way the music makes them feel. Discussions include what makes a piece of music emotional and what about the music develops a sense of happiness, sadness, fear, longing or excitement. Students will listen to the piece of music, play the music, and then reflect on those emotions and ultimately write their own story of what that piece of music means to them. I designed these lessons for my high school band students based on new ideas I gained from study during my master's program in the area of philosophy and instrumental rehearsal techniques. Two major developments in my teaching are directly due to the ongoing study of advanced rehearsal techniques combined with specific techniques used in all areas of percussion playing as well as the study of history and philosophy in music education. Through my studies in Rehearsal Techniques, we discussed the fact that music is feelings described in sound and how communication, non-verbal and verbal, is extremely important in rehearsals. Dr. Tracz went over the master teacher perspective in which good teachers tell, excellent teachers explain and demonstrate, and the master teacher inspires. I love that idea and want to become that master teacher for my students. Furthermore, the study of Philosophy in Music Education taught by Dr. Payne, really got me thinking about the way my students think and interact with music. I discovered that my teaching style reflects the thoughts of Bennett Reimer and Elliott Eisner the most. I agree with Eisner in thinking that arts educate the whole child and Reimer’s idea of music education existing to make musical experiences in all their various manifestations available to all people. Before I decided to get my master's degree I did not think about students’ emotions, feelings and thoughts about the music very often. I was concerned about technique, correct notes and rhythms and intonation. It has now become clear that studying these reactions about music in all my band classes benefit the students overall mental health as well as mine.
Keywords: Reflections on different styles of music; Emotion and feeling; High school band